2015
DOI: 10.1007/s10620-015-3521-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C Infection as a Risk Factor for Renal Cell Carcinoma

Abstract: Patients with chronic HCV are at heightened risk of RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 22 publications
0
36
0
3
Order By: Relevance
“…In a cohort study of 67,000 HCV-tested people, hepatitis C infection was associated with an approximately 80% increased risk of RCC (adjusted hazard ratio 1.77, 95% CI 1.05-2.98) [10] . A recent case-control study of 140 patients with RCC and 100 patients with colon cancer (controls) suggested that HCV infection was a significant risk factor for RCC [12] . The association of HCV with RCC can be attributed to the HCV virus core protein and the NY-REN-54 protein [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cohort study of 67,000 HCV-tested people, hepatitis C infection was associated with an approximately 80% increased risk of RCC (adjusted hazard ratio 1.77, 95% CI 1.05-2.98) [10] . A recent case-control study of 140 patients with RCC and 100 patients with colon cancer (controls) suggested that HCV infection was a significant risk factor for RCC [12] . The association of HCV with RCC can be attributed to the HCV virus core protein and the NY-REN-54 protein [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al [10] suggested that the average age of HCV carriers with RCC was significantly lower than that of HCV-negative individuals with RCC. In addition, Gonzalez et al [12] reported that RCC patients with a positive HCV status were significantly younger than RCC patients without HCV infection. In our study, we also observed that patients with RCC who were positive for HBV or HCV were significantly younger than RCC patients without chronic hepatitis virus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV infection was highly associated with development of RRC (OR= 24.2). 61 This finding is supported by the Kaiser Permanente retrospective registry as well. 56 …”
Section: Introductionmentioning
confidence: 61%
“…The statistical heterogeneity was high with an I 2 of 77%. The association between RCC and HCV was marginally insignificant after the sensitivity analysis including only studies with confounder adjustment[16,18-20,22] with a pooled RR of 1.50 (95%CI: 0.93-2.42, I 2 =64%), as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 97%